CASE REPORTA large pseudoaneurysm of the left cardiac ventricle in a 57-year-old patient after urgent coronary artery bypass grafting and surgical mitral valve replacement due to acute myocardial infarction - Wieczorek, Joanna; Mizia-Stec, Katarzyna; Rybicka-Musialik, Anna; Janusiewicz, Piotr; Malinowski, Marcin; Deja, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
We present a rare case of a left ventricular pseudoaneurysm in a patient after inferior wall myocardial infarction. The infarction was complicated with acute mitral insufficiency, pulmonary edema, and cardiogenic shock. Urgent surgical mitral valve replacement and coronary artery bypass grafting were performed. After several months, the patient was hospitalized again because of deterioration of exercise tolerance and symptoms of acute congestive heart failure. A large pseudoaneurysm of the left ventricle was recognized and successfully treated surgically.